Capital Market Institutions and Venture Capital: Do They Affect Unemployment and Labour Demand? - Rainer Fehn; Thomas Fuchs (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper analyses the influence of the capital market on the labour market. Especially the impact of start-up financing on the structure of unemployment is of interest. We use a cross-country panel data analysis to examine how venture capital investment influences disaggre-gate unemployment. As we expected, venture capital investment has different influences on sectoral-, educational- and occupational-specific unemployment. We suggest, on the basis of the regression results that venture capital investment is a catalyst of structural change and has contributed to the faster growing internet and new economy sector in countries like the U.S. that have a well-developed venture capital market.
Keywords: 330; Labor markets; venture capital; employment; new economy; panel analysis